2000
DOI: 10.1055/s-2000-6303
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Allylation and Crotylation Reactions of Aldehydes with Potassium Allyl- and Crotyltrifluoroborates under Lewis Acid Catalysis

Abstract: Potassium allyl-and crotyltrifluoroborates react with aldehydes in a process catalyzed by a variety of Lewis acids, to give the corresponding homoallylic alcohols. Of the Lewis acids examined, BF 3 ◊OEt 2 , used either stoichiometrically or catalytically, was found to most efficiently catalyze this reaction. The air and moisture stable potassium organotrifluoroborate salts react with a variety of alkyl, a-or b-substituted alkyl, and aryl aldehydes, and lead to the adducts in high yield and with high diastereos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(47 citation statements)
references
References 5 publications
1
46
0
Order By: Relevance
“…To that end, ar ange of chelatable metal halides and triflates were screened ( Table 3). Inspired by Batey's additions of allyltrifluoroborates to achiral aldehydes [29] and N-sulfonyl imines, [30] as wella sd iastereoselective additions to chiral aldehydes, [31,32] we substituted allylBF 3 Kf or allylTMS. [20] Our calculations predicted ah ighly organized zinc chelate structure that is consistent with the high The relative configuration was established by X-ray crystallography (see SupportingInformation).…”
Section: Resultsmentioning
confidence: 99%
“…To that end, ar ange of chelatable metal halides and triflates were screened ( Table 3). Inspired by Batey's additions of allyltrifluoroborates to achiral aldehydes [29] and N-sulfonyl imines, [30] as wella sd iastereoselective additions to chiral aldehydes, [31,32] we substituted allylBF 3 Kf or allylTMS. [20] Our calculations predicted ah ighly organized zinc chelate structure that is consistent with the high The relative configuration was established by X-ray crystallography (see SupportingInformation).…”
Section: Resultsmentioning
confidence: 99%
“…15 Adapting this protocol would allow the use of air- and moisture stable organotri-fluoroborates in the borazine synthesis, 16 which was expected to expand the range of functional groups and subunits that could be incorporated. Thus, aryl as well as alkyl-, alkenyl-, and alkynyltrifluorobo-rate substrates were envisioned as suitable precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Following the pioneering work by Petasis on the 1,2-addition of alkenyl- and arylboronic acids to imines 20 and further complemented by outstanding related work including that of Batey, 21 Langlois, 22 and Raeppel 23 , the nucleophilic addition of organoboronic acid derivatives to oxocarbenium ion has gained much interest. 24 Furthermore, recent reports have shown that such reactions can be rendered enantioselective.…”
Section: Introductionmentioning
confidence: 99%